Deletion viral genome diversity among bovine viral diarrhea virus (BVDV) 1a and 1b strains - David J. Holthausen; Darrell O. Bayles; John D. Neill; Rohana P. Dassanayake; Shollie M. Falkenberg; Harish Menghwar; Eduardo Casas (Virology Journal)
Abstract Background Bovine viral diarrhea virus (BVDV) is a pervasive respiratory pathogen of economic concern for the cattle industry. Transplacental infection results in abortion or the establishment of a tolerant and persistent viral infection. Deletion viral genomes (DelVGs) are naturally occurring products of the viral replication process. These deletion viral genomic transcripts are generated with truncations of various sizes that severely impede or prevent self-replication. DelVGs have been implicated in the establishment of viral persistence. Methods We used a bioinformatic pipeline to discover the presence of BVDV DelVGs. These DelVGs were identified via analysis of Illumina MiSeq reads from 74 BVDV1 field isolates from two closely related subgenotypes and from an in vitro passage of a BVDV1a virus at two different multiplicities of infection (MOI). Results After the identification of DelVGs, we assessed their phylogenetic linkage to begin elucidating potential roles in the viral life cycle and persistence. BVDV1a viruses queried generate significantly more DelVGs, with 52% of 5’ and 3’ junctions occurring in the core/capsid (C) region and a major NS2-NS5B deletion species. In contrast, the BVDV1b viruses generated significantly fewer DelVGs, especially a reduction in C region deletions. In vitro passaging of the BVDV1a Singer virus demonstrated that MOI significantly impacts the generation of DelVGs, with higher MOIs generating more DelVGs and a different deletion profile. Conclusions Here, we report that the BVDV1a and BVDV1b subgenotypes generate diverse species of DelVGs. These DelVGs may play key roles in BVDV evolution and the establishment of persistence during transplacental infection.